Validation of the Moroccan arabic version of the low anterior resection syndrome score - Hajar Essangri; Mohammed Anass Majbar; Amine Benkabbou; Laila Amrani; Raouf Mohsine; Amine Souadka (BMC Gastroenterology, 2020)
Abstract Background Sphincter sparing surgery is oftentimes associated with bowel dysfunction complaints, namely the low anterior resection syndrome (LARS). The LARS questionnaire is widely used to assess this syndrome. The aim of this observational study is to translate this tool into arabic and test its psychometric properties in rectal cancer patients, in order to ease its use in clinical practice and future research. Methods The LARS questionnaire was translated to arabic and administered to a total of 143 patients. A subgroup of 42 patients took the test twice for test-retest reliability. Internal consistency was examined through cronbach’s alpha. The score results were correlated to the EORTC QLQ-C30 questionnaire for convergent validity assessment, while discriminant validity was established through the ability of the LARS score to differentiate patients with different clinical and pathological criteria. Results The Moroccan Arabic version of the LARS score was completed by 143 patients. The internal consistency was demonstrated through a cronbach alpha score of 0.66. The agreement between the test and retest was established by a Bland Altman plot with 95% limits of agreement. 85.6% of patients remained in the same LARS category. The LARS score showed negative correlation with all five of the QLQ-C30 functional scales as well as positive correlation to the diarrhea symptom scale. The questionnaire score differed between patients according to their tumor location, chemoradiotherapy, type of mesorectal excision and anastomosis. Conclusion The Moroccan Arabic version of the LARS score shows good psychometric properties and can be used for bowel dysfunction assessment in clinical and research settings.